Koordinasi Antar Bidang dan Kerjasama Badan Kepegawaian Daerah dengan Organisasi Perangkat Daerah Lainnya di Lingkungan Pemerintah Kabupaten Probolinggo dalam Pemutakhiran Data Sistem Informasi Administrasi Pegawai (SIAP Online) - Adhitama, Mirza Surya (Jurnal Ilmiah Administrasi Publik, 2021)
With the presence of Presidential Instruction No. 3/2003 concerning to thr National e-Government Development Policies and Strategies, the President instructed the implementation of E-Government development nationally in accordance with their respective duties, functions and authorities. The concrete step in the implementation of e-government in Probolinggo Regency, especially the Regional Personnel Agency is the establishment of an Online Employee Administration Information System (SIAP Online). This study aims to describe the Collaboration of Regional Personnel Agencies with other Regional Apparatus Organizations (OPD) as well as Coordination between fields in the Regional Personnel Agency in utilizing SIAP Online. Based on the research that has been done, the results show that the collaboration carried out by the Regional Personnel Agency in the framework of presenting staffing data has gone well. This is due to the support in the form of regional regulations and regent regulations that facilitate the cooperation process with other OPDs.